Correction: Inactive matrix gla protein plasma levels are associated with peripheral neuropathy in Type 2 diabetes. - Anne-Caroline Jeannin; Joe-Elie Salem; Ziad Massy; Carole Elodie Aubert; Cees Vemeer; Chloé Amouyal; Franck Phan; Marine Halbron; Christian Funck-Brentano; Agnès Hartemann; Olivier Bourron (PLoS ONE, 2020)
[This corrects the article DOI: 10.1371/journal.pone.0229145.].